Combining typeface and color to prime specific taste expectations - Lee, BP; Spence, CJ (American Psychological Association, 2023)
The effects of color and typeface on people’s taste expectations have been well documented in the literature on crossmodal correspondences. However, research on the interaction between different visual features when they are collectively associated with specific taste qualities is scarce. Here, an online study is presented that examines the combined effect of color and typeface by simultaneously manipulating the color scheme and font curvilinearity of text stimuli. The findings confirm the main effects of color hue and typeface curvilinearity in terms of modulating the strength of association with the four basic taste qualities (sweet, sour, salty, and bitter). The results revealed that the congruent pairings of color hue and typeface curvilinearity induced stronger taste associations. In particular, the combinations of congruent visual text properties further modified the strength of taste association with sweet (p < .005), sour (p < .0001), bitter (p < .001), and with a borderline-significant effect in the case of salty (p = .054). There was no effect of typeface curvilinearity on sour ratings when the text stimuli were presented in colors that had previously been documented to associate with sourness. Overall, the effects of color and typeface on taste expectations induced by text stimuli follow the documented patterns of hue–taste and curvilinearity–taste correspondences. Although both color and typeface exerted a significant effect on taste expectations, the evidence presented here suggests that the color scheme tends to dominate over typeface curvilinearity when determining the taste quality that people associate with a given text stimulus.